Formulation, In Vitro And In Vivo Evaluation Of Cosmetic Nano-Cream From Virgin Coconut Oil, Kojic Acid Dipalmitate And Emulium Kappa - Al-Edresi, Sarmad Sabah Nasser (2009)
Virgin Coconut Oil (VCO)-in-water stabilized by Emulium Kappa® (EK) as an emulsifier was used to prepare a cosmetic cream. Kojic acid dipalmitate (KDP) dissolved in VCO was the whitening ingredient. The final characteristic of the cream formulation depends on the ratio of the oil phase, emulsifier/coemulsifier and water which are considered as the main variables. Ternary phase diagram with contour graphics was used to assess the effects of variable changes. The system was designed by using Scheffe model.